PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP PROFITABILITAS PADA PT INDOFARMA PERSERO TBK - A’yun, Qurratu; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to examine the effect of liquidity and solvability on profitability at PT Indofarma (Persero) Tbk during the period 2014–2019. The research uses an associative method with a quantitative approach. The data used in this study are secondary data obtained from the company’s financial statements. Data analysis techniques include multiple linear regression, correlation coefficient, determination coefficient, and hypothesis testing. The results of the study indicate that liquidity has a positive effect on profitability, while solvability has a negative effect on profitability. The regression equation obtained is Ŷ = 0.156 + 0.013 X1 − 0.117 X2. The correlation coefficient value of 0.963 shows a very strong relationship between liquidity, solvability, and profitability. Furthermore, the coefficient of determination of 0.877 indicates that 87.7% of the variation in profitability can be explained by liquidity and solvability, while the remaining 12.3% is influenced by other variables outside this study.The results of hypothesis testing show that liquidity does not have a significant effect on profitability, while solvability has a significant effect on profitability. These findings imply that the company needs to pay more attention to managing its solvability to improve profitability performance and maintain financial stability.